2007
DOI: 10.1590/s1519-566x2007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de fatores ambientais sobre a mirmecofauna em comunidade de restinga no Rio de Janeiro, RJ

Abstract: -The effects of environmental factors on the richness, diversity and abundance of ants were studied in the Restinga da Marambaia, south coast of Rio de Janeiro State, Brazil. The samples were taken using pitfall traps in August/2004 (winter) and March/2005 (summer) in three different vegetation types: (1) herbaceous ridge palmoid (homogeneous habitat); (2) shrub dune thicket and (3) ridge forest (heterogeneous habitats). At each habitat a range of environmental attributes was recorded: soil temperature and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 14 publications
(23 reference statements)
2
29
0
14
Order By: Relevance
“…Esta informação confirma o potencial da armadilha Moericke na captura de Hymenoptera, entretanto, diversos autores sugerem o uso combinado de diferentes métodos de coleta para amostragem de himenópteros (Noyes, 1989;Mazón & Bordera, 2008 É interessante salientar que 88,60% (1.500) dos exemplares de Formicidae obtidos neste estudo foram capturados nas armadilhas Pitfall (Tabela 2). Esta armadilha é bastante utilizada para estudos mirmecológicos (Vargas et al, 2007;Cerdá et al, 2009) e captura em geral insetos com hábitos edáficos. Pompilidae (33,33%) e Platygastridae (32,04%) também foram bem representados neste tipo de armadilha, indicando que estas famílias possivelmente têm hábitos edáficos, muito provavelmente em busca de hospedeiros, como, por exemplo, aranhas e grilos (Masner & Hanson, 2006).…”
Section: Científicasunclassified
“…Esta informação confirma o potencial da armadilha Moericke na captura de Hymenoptera, entretanto, diversos autores sugerem o uso combinado de diferentes métodos de coleta para amostragem de himenópteros (Noyes, 1989;Mazón & Bordera, 2008 É interessante salientar que 88,60% (1.500) dos exemplares de Formicidae obtidos neste estudo foram capturados nas armadilhas Pitfall (Tabela 2). Esta armadilha é bastante utilizada para estudos mirmecológicos (Vargas et al, 2007;Cerdá et al, 2009) e captura em geral insetos com hábitos edáficos. Pompilidae (33,33%) e Platygastridae (32,04%) também foram bem representados neste tipo de armadilha, indicando que estas famílias possivelmente têm hábitos edáficos, muito provavelmente em busca de hospedeiros, como, por exemplo, aranhas e grilos (Masner & Hanson, 2006).…”
Section: Científicasunclassified
“…Vargas et al (2007) collected in RM four more new species, and Feitosa and Brandão (2008) reported another one (Table 1). Out of the seven genera, Prionopelta and Proceratium have not been recorded for the state yet (Table 2).…”
mentioning
confidence: 99%
“…Most known ant species live in the soil and in the leaf litter of tropical forests (Wall and Moore 1999;Silva and Silvestre 2004). Standardized sample design helped to increase our knowledge on the ant fauna of Brazilian biomes, in particular leaf litter ants of Atlantic Forest (see Majer et al 1997;Veiga-Ferreira et al 2005;Vargas et al 2007). Association of sampling techniques, such as Winkler's extractors and pitfall traps (Olson 1991;Bestelmeyer et al 2000), may sample 75 % of all ant species found in leaf litter, a representative sample for many ecological studies that also allows new records of species.…”
mentioning
confidence: 99%
See 2 more Smart Citations